The role of Islamic leadership in vitalizing high morale in the workplace / Muliati Usman ... [et al.] - Usman, Muliati; Harmen, Hamdi; Rakhmawati, Lenny; Farid, .; Suryani, Ade Irma (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
Organizations are increasingly involved in the struggle of what is often known as an 'ethical dilemma', a condition that requires a clear definition of right and wrong actions caused by lines or boundaries that are increasingly blurred than before. Indeed, leadership and management are human activities as the art and skill of utilizing productive resources to achieve desired goals. Furthermore, it becomes clear, one of the factors that influence the formation of the moral character of employees is the role of spirituality in the work environment and the humility of leaders. The purpose of this research is to explore the relationship between Islamic leadership and high morale in the workplace. In relevant conditions, the role of a leader is as the person who leads and the person who manages to translate the vision, direction, and plans into effective actions for the progress of the organization. Thus, the role of the leader is key to shaping and developing organizational culture. This study is a theoretical development to form the basis for empirical studies of leadership models. This study indicated that Islamic values have a significant effect to boost high morale in the workplace. The role of the leadership needs to be empowered in order to build workers' awareness of the importance of Islamic values as a principle of life. Thus, this study expands the literature in the field of leadership styles that explores Islamic values in increasing morale in the workplace.